Symmetry breaking and structural polymorphism in a bacterial microcompartment shell protein for choline utilization. (14th September 2020) - Ochoa, Jessica M.; Nguyen, Vy N.; Nie, Mengxiao; Sawaya, Michael R.; Bobik, Thomas A.; Yeates, Todd O.
Abstract: Bacterial microcompartments are protein‐based organelles that carry out specialized metabolic functions in diverse bacteria. Their outer shells are built from several thousand protein subunits. Some of the architectural principles of bacterial microcompartments have been articulated, with lateral packing of flat hexameric BMC proteins providing the basic foundation for assembly. Nonetheless, a complete understanding has been elusive, partly owing to polymorphic mechanisms of assembly exhibited by most microcompartment types. An earlier study of one homologous BMC shell protein subfamily, EutS/PduU, revealed a profoundly bent, rather than flat, hexameric structure. The possibility of a specialized architectural role was hypothesized, but artifactual effects of crystallization could not be ruled out. Here we report a series of crystal structures of an orthologous protein, CutR, from a glycyl‐radical type choline‐utilizing microcompartment from the bacterium Streptococcus intermedius . Depending on crystal form, expression construct, and minor mutations, a range of novel quaternary architectures was observed, including two spiral hexagonal assemblies. A new graphical approach helps illuminate the variations in BMC hexameric structure, with results substantiating the idea that the EutS/PduU/CutR subfamily of BMC proteins may endow microcompartment shells with flexible modes of assembly.